Chapter 7 Community identity and mobilisation Roma migrant experiences in Manchester - Matras, Yaron (Taylor & Francis, 2018)
Romani political mobilisation is now an established part of the civil society landscape across Europe. It has given rise to various forms of political participation, with Romani NGOs taking up consultative roles in a number of countries, as well as in inter-governmental organisations. Models of direct political representation of Roma through a kind of quota system exist at the level of local government in Hungary and in the national elections in Romania, and a number of parliamentarians of Romani background have held direct mandates in national legislatives and in the European Parliament